Identification of genetic defects in pulmonary arterial hypertension by a new gene panel diagnostic tool - Song, Jie; Eichstaedt, Christina; Rodríguez Viales, Rebecca; Benjamin, Nicola; Harutyunova, Satenik; Fischer, Christine; Grünig, Ekkehard; Hinderhofer, Katrin (Clinical science, 2016)
We developed a new candidate gene approach for pulmonary arterial hypertension based on a customized kit and new sequencing technologies. In this manner we identified mutations in routinely assessed genes and one additional gene in PAH patients.
Gesehen am 12.05.2020